DONATION SYSTEM FOR ISLAMIC PRIMARY SCHOOL - Siti Aishah Muhammed Suzuki; Fauziah Abdul Wahid (Journal of Islamic, Social, Economics and Development, 2020)
The web-based system is a system that use internet server as communication mode to deliver information and services to the user. The requirement includes technology and sophisticated tools to deliver appropriate objectives in order to determine the features and design requirements, for example, to develop the Donation System for Islamic Primary School, design and development and applying the suitable security features into the system. Mostly a system usually focus on gaining attraction solely in direct and specific needs and lack in advertising any option provided. In this system, web development is used not only to deliver a message and view to the public about concurrent activities that were running in the Islamic primary school but they can also view many other option for fundraising. In general, a fundraising website was conducted for the school to publish their social activities for donation purposes. It also will ensure the effectiveness of doing it online rather than having limited time on blasting the news with zero responsive. The methodology applied into this system was Waterfall model of software development life cycle (SDLC), which comprises five phases for ensuring its process practicality. Security including blowfish hashing technique, error handling and disable right click was implemented as part of security development. Regard with the system development, language used was Hypertext Mark-up Language (HTML), Hypertext Pre-processor (PHP), Cascading Style Sheet (CSS) and JavaScript for developing the system.